Socially Integrated, Eco-Mimic Reversal of Global Warming - Butterworth, Bill (Journal of Technology Innovations in Renewable Energy, 2014)
The recent announcements of the IPCC [1] have indicated that many, indeed most, climatologists accept that climate change is happening, rapidly and the potential consequences are significant. This paper examines the potential contribution to reduction and reversal of global warming by feeding the photosynthetic process with urban wastes, and how this can be integrated into existing or developable social structures in a way that allows normal economic drivers to produce rapid, large scale, sustainable results.